Pengaruh Harga Dan Lokasi Terhadap Volume Penjualan Ikan Di Pasar Kecamatan Deli Tua Kab. Deli Serdang Sumatra Utara - Fitri Dalmayani; Rahmi Syahriza; Reni Ria Armayani Hasibuan (Universitas Dharmawangsa, 2023)
ABSTRACT Â This study aims to determine the effect of price and location on sales volume in Pasar Kecamatan Deli Kab. Deli Serdang, North Sumatra. This study uses a quantitative method with a descriptive approach. The population in this study were fish sellers in the Deli Tua sub-district market. The sample in this study were 58 respondents. Data collection methods in this study using questionnaires and interviews. The analytical method used was multiple linear regression analysis with data analysis using SPSS version 22. The results showed that: 1) Prices have a positive and significant effect on the volume of fish sales in the Deli Tua sub-district market, this is indicated by the regression coefficient which has a positive value, namely 0.108 or 10.8% and the tcount value is greater than ttable, namely 0.784 > 0.678. 2) Location has a positive and significant effect on the volume of fish sales at the Deli Tua sub-district market. This is indicated by the regression coefficient which is positive, namely 0.783 or 78.3%% and the tcount value is greater than ttable, namely 5.487 > 0.678. 3) Price and location have a simultaneous effect on the volume of fish sales in the Deli Tua sub-district market, this is shown by the results of the F (simultaneous) test with a Fcount value that is greater than Ftable, namely 9.843> 3.16 and also a coefficient value of 0.606, in other words, the effect the price and location of the sales volume of fish in the Deli Tua sub-district market amounted to 60.6% while the remaining 39.4% of the volume of fish sales in the Deli Tua sub-district market was influenced by other factors.Â Keywords : Price, Location, Sales Volume